Reliability and validity of the performance index evaluation among men's and women's college basketball players - Barfield, J.-P.; Johnson, R. J.; Russo, P.; Cobler, D. C. (The Journal of Strength and Conditioning Research, 2007)
The Performance Index Evaluation (PIE) is a basketball-specific assessment of physical performance. The battery consists of items typically included in sport assessments, such as agility and power, but also addresses an often-overlooked performance component, namely, core strength. The purpose of this study was to examine the reliability (test-retest, interrater), validity (criterion-related, construct-related), and practice effect of the PIE among men's and women's college basketball players. Test-retest estimates were moderate for men (intraclass correlation coefficient [ICC] = 0.79) and poor for women (ICC = 0.35), but interrater reliability was high (ICC = 0.95). Criterion-related validity evidence (i.e., relationship between PIE and playing time) was weak, but construct-related evidence was acceptable (i.e., college players had higher scores than high school players). A practice effect was also demonstrated among men. In conclusion, reliability of the battery should be improved before its use is recommended among college basketball players. Additionally, the battery does not appear to be a predictor of performance but does appear to distinguish between skill levels.